2001
DOI: 10.1117/12.431217
|View full text |Cite
|
Sign up to set email alerts
|

<title>Microablation of pure metals: laser plasma and crater investigations</title>

Abstract: Crater shapes and plasma plume expansion in the interaction of femtosecond (70 fs), picosecond (20 ps) and nanosecond (6 ns) laser pulses (wavelengths-800 nm; 400 nm and 266 nm for femtosecond Ti-Al203 laser ; 1064 nm, 532 nm and 266 nm for nanosecond and picosecond Nd-YAG lasers; mode-nearly TEM00; waist diameter-of the order of 1 0 jim) with various pure metals in air and noble gases at atmospheric pressure were studied. The craters formed at the surfaces were measured by an optical microscope profilometer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This is in correlation with the results of our previous studies [17]. Crater volumes, depths and diameter were the same for metal samples irradiated by pulses with 50 fs -1 ps durations with identical experimental parameters [10][11]. In addition, the analysis of plasma images with 50 fs or 1 ps pulse durations has demonstrated that plasma reheating was identical in both the cases [16][17].…”
Section: Calibration Curvessupporting
confidence: 89%
See 2 more Smart Citations
“…This is in correlation with the results of our previous studies [17]. Crater volumes, depths and diameter were the same for metal samples irradiated by pulses with 50 fs -1 ps durations with identical experimental parameters [10][11]. In addition, the analysis of plasma images with 50 fs or 1 ps pulse durations has demonstrated that plasma reheating was identical in both the cases [16][17].…”
Section: Calibration Curvessupporting
confidence: 89%
“…The efficiency of Al sample ablation with 50 fs -1 ps pulses does not depend on the laser pulse duration [10][11]13]. For 50 fs pulses, the maximum pulse energy did not exceed 40 µJ so that the undesirable nonlinear effects inherent to fs laser propagation in air (10 µm waist spot) may be avoided.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The two major mechanisms significant for sampling of solids are melting followed by vaporisation and explosion of macroparticulates caused by mechanical effects, which can depend on grain size and density of each sample. Our previous results [33] showed that metals with lower melting temperature give greater crater volumes, which suggested that an important role in the crater formation should be attributed to processes dealing with plasma -target interaction and liquid matter ejection. Thus, we can suppose that liquid matter ejection could play an important role in the ablation process of metals explaining the presence of a protrusion along the crater boundary.…”
Section: Elementmentioning
confidence: 98%